2022
DOI: 10.1002/lno.12161
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nitrogen isotope fractionation during nitrification based on a coastal time series

Abstract: Isotopic enrichment factors are key to using stable isotope signatures in biogeochemical studies. However, these are typically determined in laboratory experiments and their applicability to environmental conditions is difficult to test. Here, we analyzed nitrogen stable isotope changes associated with nitrification in a coastal basin using weekly time-series measurements of δ 15 N in particulate nitrogen, ammonium, nitrite, and nitrate. Two year-long time series were selected as contrasting natural experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Haas et al. (2022) suggested that suspended POM may contribute to the observed N‐isotopic differences with steady δ 15 N PON values observed in near‐surface waters with a simultaneous δ 15 N PON increase in the bottom water. Alternative reasons for this observation may be that sinking POM has different carbon/nitrogen compositions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Haas et al. (2022) suggested that suspended POM may contribute to the observed N‐isotopic differences with steady δ 15 N PON values observed in near‐surface waters with a simultaneous δ 15 N PON increase in the bottom water. Alternative reasons for this observation may be that sinking POM has different carbon/nitrogen compositions.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, chl a increased from January to March and remained relatively high until July and then exhibited a slight decrease, while POC and PON increased from January to July and then decreased. Haas et al (2022) suggested that suspended POM may contribute to the observed N-isotopic differences with steady δ 15 N PON values observed in near-surface waters with a simultaneous δ 15 N PON increase in the bottom water. Alternative reasons for this observation may be that sinking POM has different carbon/nitrogen compositions.…”
Section: Environmental Characteristics During the Investigation Periodmentioning
confidence: 86%
“…We attribute this lack of isotopic difference to the comparatively short integration time of much of the suspended PON pool (that we assume comprised mainly phytoplankton) compared to zooplankton in general and foraminifera in particular (Eppley et al, 1983;Altabet and McCarthy, 1985;Fasham et al, 1990;Capone et al, 2008). Indeed, δ 15 NPON can be rapidly altered (within hours to days; Savoye et al, 2003;Treibergs et al 2014) by several processes, including a switch in the dominant N form consumed by phytoplankton (i.e., from nitrate to ammonium) (Liu et al, 2007;Treibergs et al 2014) and mixing with surrounding water masses (Mino et al, 2020;Haas et al, 2022). The isotopes of suspended PON are further discussed in section 4.3.4 below.…”
Section: Controls On Foraminifer δ 15 Nmentioning
confidence: 98%
“…The Sackville River delivers freshwater into the head of the basin and at its seaward end the basin is connected to the outer Halifax Harbour and the Scotian Shelf via a 20 m deep sill. The freshwater input (5.3 m 3 s -1 ) is small compared to the mean tidal volume (2.5 × 10 7 m 3 ) and the total basin volume (5.1 × 10 8 m 3 ) (Petrie and Yeats, 1990;Haas et al, 2022). The presence of the sill restricts the estuarine circulation to the upper 20 m and the bottom water can become isolated from the surface layer due to stratification, leading to development of seasonal hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…This includes weekly CTD casts for hydrographic (T, S) and several chemical properties in both the surface (1, 5, 10m) and bottom (60m) waters. Bedford Basin has been the focus of numerous studies examining geological (Miller et al, 1982;Buckley and Winters, 1992;Fader and Miller, 2008), chemical (Shi and Wallace, 2018), climatological (Li and Harrison, 2008), biogeochemical (Conover, 1975;Hargrave, 1978;Taguchi and Hargrave, 1978;la Roche, 1983;Azetsu-Scott and Johnson, 1994;Punshon and Moore, 2004;Li et al, 2010;Burt et al, 2013;Georges et al, 2014;Haas et al, 2021;Haas et al, 2022;Robicheau et al, 2022) and environmental (Rao et al, 1993;Pan and Subba Rao, 1997;Scott, 2005;AMEC, 2011;Lacasse et al, 2013;Vercaemer and Sephton, 2014) aspects of the basin. Several of these studies have focussed on processes influenced by the transient hypoxic characteristics of the basin.…”
Section: Introductionmentioning
confidence: 99%